SUCCESS OF DEVELOPMENT OF SERVICES AND PROVISION OF RECREATIONAL SERVICES - Карлова, Елена (SWorldJournal, 2020)
Abstract. The article reveals the ideas of recreation development and the process of providing recreational services. In the field of services, there are a number of problems and imbalances in the development of the recreational industry, associated with